A Material Perspective of Rechargeable Metallic Lithium Anodes. Issue 13 (14th February 2018) - Li, Bin; Wang, Ying; Yang, Shubin
Abstract: Rechargeable lithium‐based batteries are long considered as the most promising candidates for application in various electronic devices, electric vehicles, and even electrical grids owing to their ultrahigh energy densities. However, to date, metallic lithium‐based batteries are still far from practical applications due to the low Coulombic efficiency and fast capacity decay of lithium anodes. The poor electrochemical performances of metallic lithium anodes are inherently related to random growth of lithium dendrites and infinite volume charge of lithium anodes. In this review, the failure mechanisms of metallic lithium anodes are summarized and ascribed to the unstable and inhomogeneous solid electrolyte interphase, uneven distributions of electric field, and lithium‐ion flux during the lithium plating processes. Correspondingly, efficient strategies for mitigating these problems, including surficial engineering, electric field, and lithium‐ion flux regulation are discussed from the perspective of anode materials. Finally, an outlook is proposed for the design and fabrication of next‐generation rechargeable metallic lithium anodes that aims to address the intrinsic problems of metallic lithium anodes. Abstract : Rechargeable metallic lithium batteries attract tremendous attention due to the ultrahigh energy density of metallic lithium anodes. In this review, the failure mechanisms of metallic lithium anodes and the corresponding strategies for their mitigation, including surficial engineering, electric field, and lithium‐ion flux regulation are systematically summarized from the perspective of electrode materials.